2022
DOI: 10.28991/hij-2022-03-04-06
|View full text |Cite
|
Sign up to set email alerts
|

Are Activation Teaching Methods Really Effective?

Abstract: The primary aim of the presented paper is to demonstrate the effectiveness of activation teaching methods in the teaching of technical subjects at secondary vocational schools through pedagogical research using a pedagogical experiment. The effectiveness of the activation teaching methods is demonstrated in the Integrated Rescue System subject taught in the field of Security and Legal Activity. The object of the research are pupils who were 2nd year pupils in the 2019/2020 school year, as well as teachers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…The results showed that VR exercises were comparable to human-guided exercises in terms of motion and fitness parameters, and the participants reported feelings of enjoyment, engagement, interest, easiness, comfort, and level of effort. The researchers suggested that head-mounted VR has promising potential to support physical activity for people living with dementia [56][57][58].…”
Section: -3-user Experience and Engagementmentioning
confidence: 99%
“…The results showed that VR exercises were comparable to human-guided exercises in terms of motion and fitness parameters, and the participants reported feelings of enjoyment, engagement, interest, easiness, comfort, and level of effort. The researchers suggested that head-mounted VR has promising potential to support physical activity for people living with dementia [56][57][58].…”
Section: -3-user Experience and Engagementmentioning
confidence: 99%